The Universal Declaration of Human Rights: A Tribute to Its Architects. (3rd April 2017) - McFarland, Sam
Abstract : The Universal Declaration of Human Rights, adopted by the United Nations on December 10, 1948, had five key architects: American Eleanor Roosevelt, Lebanon's Charles Malik, China's Peng-chun Chang, Canada's John Humphrey, and France's René Cassin. They represented diverse cultures and religions, and often disagreed sharply. This article offers a short history of their work and achievement.